Integrated treatment options for male perpetrators of intimate partner violence. (21st January 2017) - Crane, Cory A.; Easton, Caroline J.
Abstract: Issues: Male‐to‐female intimate partner violence remains a worldwide public health issue with adverse physical and psychological consequences for victims, perpetrators and children. Personality disorders, addiction, trauma and mood symptoms are established risk factors for intimate partner violence perpetration and factor prominently into a recovery‐oriented treatment approach. Approach: We reviewed the partner violence literature for detailed reports of traditional as well as innovative, integrated treatment approaches. Empirically based recommendations for intervention programs and the policies that guide intervention efforts are offered. Key Findings: Nascent research suggests that integrated treatment models utilising a holistic approach to account for psychological comorbidity and interventions that involve a motivational interviewing component appear promising in terms of significantly improving intimate partner violence treatment compliance and reducing subsequent acts of physical partner violence. Further, methodologically rigorous research is required to fully assess the benefits of traditional and integrated treatment options. Implications: We have advanced several recommendations, including the development of and exclusive reliance upon empirically supported treatments, conducting a thorough risk and needs assessment of the offender and the immediate family to facilitate appropriate treatment referrals, integrating content to foster the offender's internal motivation to change maladaptive behaviours, and attempting to minimise offender treatment burdens through the strategic use of integrated treatment models. Conclusions: Intimate partner violence is a complicated and nuanced problem that is perpetrated by a heterogeneous population and requires greater variability in integrated treatment options. [Crane CA, Easton CJ. Integrated treatment options for male perpetrators of intimate partner violence. Drug Alcohol Rev 2017;36:24–33]